INFLUENCE ANALYSIS OF SMALL AMPLITUDE LOAD CYCLE TO FATIGUE LIFE CALCULATION BASED ON FLIGHT PARAMETERS - XU KeJun; WANG YongQi; XIA YiRui; QIN HaiQin (Jixie qiangdu)
The article summed up the extraction method of load spectrum cycles based on flight parameters of aeroengine and summed up the removal methods of small cycles which speed amplitude were lower than 10%,then pointed the advantages and disadvantages of each method. Analyzed the speed cycles distribution of a certain type of aeroengine,calculated the influence of small speed cycles which amplitude is lower than 10% of high pressure rotor speed by Miner’s linear cumulative damage theory,compared the influence of different removal methods to damage calculation results and pointed the advantages and disadvantages of each method; Based on EGD-3 standards,put forward the extraction method of removing small cycles and verify its rationality by calculation,then define the sensitivity factor of removing small speed cycles in fatigue calculation as 0. 3% for a certain type of aeroengine.